Clinical guidelines for the diagnosis and treatment of lower urinary tract dysfunction in patients with spinal cord injury. (19th February 2020) - Sekido, Noritoshi; Igawa, Yasuhiko; Kakizaki, Hidehiro; Kitta, Takeya; Sengoku, Atsushi; Takahashi, Satoru; Takahashi, Ryosuke; Tanaka, Katsuyuki; Namima, Takashige; Honda, Masashi; Mitsui, Takahiko; Yamanishi, Tomonori; et al.
Abstract: The present article is an abridged English translation of the Japanese clinical guidelines for the diagnosis and treatment of lower urinary tract dysfunction in patients with spinal cord injury updated as of July 2019. The patients are adult spinal cord injured patients with lower urinary tract dysfunction; special consideration of pediatric and elderly populations is presented separately. The target audience is healthcare providers who are engaged in the medical care of patients with spinal cord injury. The mandatory assessment includes medical history, physical examination, frequency‐volume chart, urinalysis, blood chemistry, transabdominal ultrasonography, measurement of post‐void residual urine, uroflowmetry and video‐urodynamic study. Optional assessments include questionnaires on the quality of life, renal scintigraphy and cystourethroscopy. The presence or absence of risk factors for renal damage and symptomatic urinary tract infection affects urinary management, as well as pharmacological treatments. Further treatment is recommended if the maximum conservative treatment fails to improve or prevent renal damage and symptomatic urinary tract infection. In addition, management of urinary incontinence should be considered individually in patients with risk factors for urinary incontinence and decreased quality of life.